Pemanfaatan Lahan Kosong Di Posyandu Muara Sehati Desa Lubuk Bendahara Untuk Pembuatan Taman Apotek Hidup Dalam Upaya Peningkatan Kesehatan Dan Upaya Mencegah Penyebaran Pasca Covid-19 - Nur Hasnah AR; Eben Ezer Sianturi; Salsabila Salsabila; Muhammad Kevin Alfayed; Pauzia Latifah Isrul; Diba Nur Ardila; Yudha Alvarizi; Caroline Kezia; Tiara Diva Pranesti; Ria Dini Tuti Yaningsih; Elza Nurman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The College of Real Work (Kukerta) is a kind of community-focused dedication initiative aimed at enhancing the potential of the region and the role of students in society. The School of Real Work (KKN) can also serve as a forum for learning and applying scientific and technological advances done outside the campus area according to established timetables, working mechanisms, and habits. Real Work College (KKN) activities are carried out in the village of Lubuk Bendahara, Rokan IV Koto district, Hulu district of Rokan, Riau Province. The purpose of this dedication is to promote public interest in the use of live pharmaceutical plants as well as to improve the health and preserve the immune system of the population after the Covid-19 pandemic. The application methods used in community service activities are planning, observation and implementation. The result of dedication to this community is the implementation of the activities of making live pharmacy parks to be used by the community around the village in an effort to maintain and improve post-covid-19 pandemic health as well as developing public awareness of the usefulness of living pharmacy plants for improving health and immunity.